A Clinician's Guide to Fecal Occult Blood Testing for Colorectal Cancer. Issue 4 (April 2016) - Bechtold, Matthew L.; Ashraf, Imran; Nguyen, Douglas L.
Abstract : Abstract: Colorectal cancer (CRC) is a significant healthcare issue, with substantial morbidity and mortality. Screening for CRC is essential in the prevention and treatment of this disease. The two most common CRC screening modalities are colonoscopy and the stool-based occult blood test, with two types of stool-based occult blood tests: the guaiac-based fecal occult blood test (FOBT) and the immunochemical FOBT. Despite many similarities, these two stool tests are different and often are confused in clinical practice. In an effort to improve awareness of these testing modalities, this review provides extensive information on both of these FOBTs, as well as discusses comparisons in the literature between these stool-based blood tests and other screening modalities such as stool DNA and colonoscopy. Abstract : Fecal occult blood tests (FOBTs) have been a staple of colorectal cancer screening for many years. More options have become available in recent years, leading to confusion among primary care physicians and gastroenterologists. The fecal immunochemical test has been used widely as a replacement for the traditional guaiac-based FOBT for many reasons; however, the fecal immunochemical test and guaiac-based FOBT are not equivalent. This review article focuses on the differences among FOBTs with descriptions and literature comparisons in an effort to enhance understanding in clinical practice.